Answer:
Option A is correct
Explanation:
Given: FH is the altitude to the hypotenuse EG
To find: length of FH
Solution:
According to Pythagoras theorem, square of hypotenuse is equal to sum of squares of other two sides.
In
,
![\angle EHF=90^(\circ)](https://img.qammunity.org/2021/formulas/mathematics/college/fgajyz0asxw1kdbrl9c66i025tr32ritxw.png)
So,
![EF^2=EH^2+FH^2](https://img.qammunity.org/2021/formulas/mathematics/college/2ntwnl1qhky705rx9gc4w1060i3y4q04yh.png)
Put EH = 6 units and EF = 7 units
![7^2=6^2+FH^2\\49=36+FH^2\\49-36=FH^2\\13=FH^2](https://img.qammunity.org/2021/formulas/mathematics/college/ybeyrw2so7h4xmjz74dbxclt2wnrybk45h.png)
Option A is correct
Take square root on both sides
![FH=√(13)=3.606\,\,units](https://img.qammunity.org/2021/formulas/mathematics/college/u34m8dwap9owol8ent2ru8tvcf42llbk8j.png)